(untitled) (REMUNOM, 2025)
The objective of this study was to analyze scientific articles related to autoimmune uveitis associated with sacroiliitis with progression to cataract and to evaluate the importance of the correct timing of cataract surgery to obtain a satisfactory surgical result. The research was carried out by reading articles indexed in the PubMed, SciELO and LILACS databases, published between 2013 and 2025, available in free full text and without language restrictions, focusing on cataract associated with autoimmune uveitis, phacoemulsification and sacroiliitis, using the following descriptors: “autoimmune uveitis”, “cataract”, “phacoemulsification”, “sacroiliitis”, “ocular inflammation”, “intraocular lens implantation”. After analyzing the specialized literature, it was observed that inflammatory stabilization was decisive for the success of phacoemulsification with intraocular lens (IOL) implantation, with a satisfactory visual outcome. This study reinforces the importance of multidisciplinary management and prior control of inflammation for visual rehabilitation in eyes with a history of autoimmune uveitis.